Lebanese sectarianism: understanding and mitigating bias - Cross, E (2022)
Intergroup biases are correlated with an erosion of civil society, uneven distribution of public goods, sub-optimal economic outcomes, political corruption, and intergroup conflict. These negative consequences have inspired generations of researchers to devise theories to understand the nature of bias and to develop methods to mitigate such bias. The objective of this book is to apply these theories to the Lebanese context to understand the extent and nature of biases among Lebanese sectarian groups. Specifically, this book explores intergroup relations among Lebanese Christians, Shias and Sunnis. The book then tests whether bias mitigation strategies that were developed in Western contexts may ameliorate intergroup biases in Lebanon.